The Relationship Between Exercise Addiction And Beliefs İn Sports Nutritional Supplements - Hüseyin Özden Yurdakul (Türk Spor ve Egzersiz Dergisi)
Purpose: In this study, it was aimed to investigate the relationship between exercise addiction levels and attitudes of athletes against nutritional supplements. Material: A total of 257 students, 62.8% (n = 161) male and 37.4% (n = 115) female, studying in the sports science faculty of Çanakkale Onsekiz Mart University, constituted the research group. “Exercise Addiction Scale” and “Belief in Sports Nutritional Supplements Scale” were used as data collection tools. The relational screening method was used in the research. The relationship between exercise addiction and belief in sports supplements was investigated using Pearson correlation and structural equation model. Results: It was observed that the dimension of the “Postponement of Individual-Social Needs and Conflict” affects positively and significantly (β = .366, p gt; .05) the “Sport Nutritional Supplements Belief” and was statistically significant. It was found that “Tolerance Development and Passion” “Sport Nutritional Supplements Belief”, which is one of the sub-dimensions of exercise addiction, positively and significantly (β = .217, p gt; .05). According to the model, it was determined that exercise addiction affects Sport Nutritional Supplements Belief by 20.8% (R2 = .208). Conclusions: According to the research results, it was concluded that exercise addiction predicted belief in sports supplements at a positive and significant level. Considering that the students of the sports sciences will work in the field as a sports scientist in the future, it is considered important to have sufficient knowledge and equipment about exercise addiction and sports nutritional supplements.